2020
DOI: 10.3389/fonc.2020.00234
|View full text |Cite
|
Sign up to set email alerts
|

Is Hydrogen Sulfide a Concern During Treatment of Lung Adenocarcinoma With Ammonium Tetrathiomolybdate?

Abstract: Li et al. ATTM-Produced H 2 S Promotes LUAD m 6 A but also upregulated H 2 S-producing enzymes. Exogenous H 2 S application mimicked ATTM's aforementioned effects, but the effects could be weakened by zinc-induced H 2 S scavenging. Collectively, H 2 S impedes ATTM-induced anticancer effects through YTHDF1-dependent PRPF6 m 6 A methylation in lung adenocarcinoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…The latter, glutathione (see Figure 1 ) is used by cells to quench harmful free radicals and reduce oxidative stress. In addition, the former cysteine stabilizes complex structures of proteins, detoxifies heavy metals, participates in electron transfer reactions, and has other metabolic functions [ 95 , 96 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ].…”
Section: Mini Reviews On the Roles Of Dmf Bupropion Same And VImentioning
confidence: 99%
See 1 more Smart Citation
“…The latter, glutathione (see Figure 1 ) is used by cells to quench harmful free radicals and reduce oxidative stress. In addition, the former cysteine stabilizes complex structures of proteins, detoxifies heavy metals, participates in electron transfer reactions, and has other metabolic functions [ 95 , 96 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ].…”
Section: Mini Reviews On the Roles Of Dmf Bupropion Same And VImentioning
confidence: 99%
“…Epigenetic reactions are reversible chromatin (gene and protein) alterations that occur in two forms, methylation and acetylations. With methylation, gene and chromatin structures are not available for transcription by replication enzymes; however, with acetylation of lysine or arginine residues in chromatin (histones), gene sequences are available to replication enzymes and transcription may occur [ 100 , 101 , 102 , 103 , 104 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ]. To help understand and these reactions, as well as epigenetic protocols, the reader is advised to consult the text edited by Tollefsbol [ 111 ].…”
Section: Mini Reviews On the Roles Of Dmf Bupropion Same And VImentioning
confidence: 99%
“…Through searching in miRDB, we observed that 7 target genes of miR-1285-3p which score >95: AHI1, DAB2IP, BTRC, YTHDF1, TMEM41B, SIKE1, and FMO5. After reviewing the literature, we disclosed that only YTHDF1 was bound up with lung adenocarcinoma [26][27][28]. As such, we surmised that LINC00337 functioned via in uencing YTHDF1 expression in lung adenocarcinoma.…”
Section: Linc00337 Regulates the Mir-1285-3p Target Gene Ythdf1mentioning
confidence: 96%
“…2B ). Similarly, YTHDF1 knockdown partly blocks the pre-mRNA processing factor 6 (PRPF6) expression and cell growth ( 34 ). YTHDF1 positively facilitates protein synthesis by interacting with the translation machinery ( 58 ).…”
Section: M 6 a Readers In Lung Cancermentioning
confidence: 99%
“…This difference may be due to the uncertainty in gene expression between the mRNA and protein levels. This unique expression contributes to ATTM-induced increase in m 6 A in A549 cells ( 34 ). METTL3 promotes the translation of important oncogenes like EGFR in lung cancer.…”
Section: M 6 a As A Potential Therapeutic Target In Lung Cancermentioning
confidence: 99%